New pressure ulcers dressings to alleviate human soft tissues: A finite element study. Issue 3 (August 2022) - Fougeron, Nolwenn; Connesson, Nathanaël; Chagnon, Grégory; Alonso, Thierry; Pasquinet, Laurent; Bahuon, Manuelle; Guillin, Eugénie; Perrier, Antoine; Payan, Yohan
Abstract: Pressure Ulcers (PU) are real burdens for patients in healthcare systems, affecting their quality of life. External devices such as prophylactic dressings may be used to prevent the onset of PU. A new type of dressing was designed to alleviate soft tissue under pressure, with the objective to prevent PU and to improve the healing conditions of category-1 and category-2 wounds. The mechanical interactions of this dressing with a generic model of human skin/hypodermal soft tissue was simulated using the Finite Element (FE) method. Different cases with intact skin tissues and injured tissues with a category-2 PU, with and without dressings in place, were modeled. The tissues were deformed under compressive load; internal strains were computed. The results showed a clear benefit from the use of the dressing to reduce the peak internal strains both in the intact and injured tissues models by 17–25%, respectively. The intact soft tissues model was evaluated via sacral pressure measurements performed on one healthy volunteer. Results showed a good agreement between pressure measurements and estimations both with and without the dressing in place; particularly under the bony prominence and in surrounding tissues. As a conclusion, the importance of dressings to maintain a proper biochemical environment for the healing of PU is incontestable. Yet, new concepts of dressings may be developed to prevent the onset of PU, but also to provide local stress and strain reliefs and create mechanical conditions as less damaging as possible for the tissues. Highlights: Biomechanical modelling of a category-2 sacral pressure ulcers. Bi-layer dressings may help to decrease soft tissues internal strains. Validation of a finite element model using pressure measurements.